Screening Flavonoids of Ethyl Acetate Extract from Matoa Tree Bark (Pometia pinnata) Using UV-Vis Spectrophotometry Method - Budiyanto, Ratno; Kholis, Ach.; Taufiqurrahman, Taufiqurrahman (Jurnal Pijar Mipa, 2025)
Matoa tree bark is a plant that contains flavonoid chemical compounds believed to be a traditional medicine in various alternative treatments. Therefore, it is important to measure its flavonoid content. Ethyl acetate extracts were prepared using the maceration method at durations of 3 x 24 hours. The aim of this study was to determine the flavonoid compound content and levels in matoa tree bark (Pometia pinnata) using UV-Vis spectrophotometry. Qualitative analysis was carried out using NaOH reagent and the wilstater cyanidin test, both of which showed positive results for containing flavonoid compounds, indicated by an orange color change. Quantitative analysis using a regression quercetin standard curve with an R2 value of 0,9844 revealed a flavonoid content of 2.712%. These results indicate that matoa tree bark extract has a high flavonoid content and has the potential to be developed as a herbal medicine formulation.